Dissociation: understanding the dynamics of primary and secondary capacities - Veronica Mateescu (The Global Psychotherapist)
This article explores the psychological defense mechanism of dissociation within the context of trauma and micro-traumas, particularly its impact on primary and secondary capacities as defined in Positive Psychotherapy (PPT). Dissociation initially acts as a protective mechanism, allowing temporary detachment from overwhelming emotional realities. However, it can become maladaptive, disrupting the balance between primary capacities (e.g., love, trust, and hope) and secondary capacities (e.g., punctuality, honesty, and achievement). Through the framework of PPT, the study highlights how dissociation compartmentalizes psychological functioning, impairing self-integration and balance across the four domains of life: body/senses, work/achievement, relationships/contact, and future/meaning/goals. Employing therapeutic autoethnography and insights from trauma theory, this analysis demonstrates how PPT’s distinctive tools, such as differential analysis and transcultural approach, facilitate nuanced and gradual healing. PPT fosters post-traumatic growth by integrating cultural sensitivity, metaphors, and storytelling, empowering individuals to transform dissociative mechanisms into resources for resilience and balanced self-functioning. This study underscores the need for culturally informed, holistic therapeutic strategies to address the multifaceted impacts of trauma.